2011
DOI: 10.1016/j.adolescence.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding threshold effects of organized activity involvement in adolescents: Sex and family income as moderators

Abstract: The current study examined the curvilinear links between involvement in organized activities (OA) and sport activities specifically and various indicators of psychological and social development. Participants included 150 9th and 10th graders (57% females) from an urban, selective‐enrollment high school. Eligibility for admission is based on city residence, high GPA, and high scores on standardized tests and an admission exam. Findings indicated that benefits of OA involvement leveled off at approximately 5–7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 72 publications
(107 reference statements)
2
29
2
Order By: Relevance
“…In addition, these fi ndings highlight that boys and girls appear to value different activities in part because perhaps they recognize that certain types of OAs are more likely to enhance their social reputation and visibility whereas other OAs may not. Other studies have reported differential effects of OA involvement on NEW DIRECTIONS FOR CHILD AND ADOLESCENT DEVELOPMENT • DOI: 10.1002/cad adjustment for boys versus girls (Denault & Poulin, 2008;Randall & Bohnert, 2011). In addition, research suggests that girls often reap more social and emotional benefi ts from activity participation than boys (Fredricks & Eccles, 2008;Simpkins, Eccles, & Becnel, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, these fi ndings highlight that boys and girls appear to value different activities in part because perhaps they recognize that certain types of OAs are more likely to enhance their social reputation and visibility whereas other OAs may not. Other studies have reported differential effects of OA involvement on NEW DIRECTIONS FOR CHILD AND ADOLESCENT DEVELOPMENT • DOI: 10.1002/cad adjustment for boys versus girls (Denault & Poulin, 2008;Randall & Bohnert, 2011). In addition, research suggests that girls often reap more social and emotional benefi ts from activity participation than boys (Fredricks & Eccles, 2008;Simpkins, Eccles, & Becnel, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Involvement in OAs may also provide adolescents with a smaller setting within the larger school context in which to feel socially accepted and satisfi ed at a particular point in development in which these feelings of acceptance may be especially salient (e.g., Berndt, 1982). Indeed, in one study of high school students, greater duration of OA involvement was associated with lower levels of loneliness among adolescents (Randall & Bohnert, 2009), while a second study found that the benefi ts of OA involvement for social acceptance and depression were evident at moderate but not high levels of involvement (Randall & Bohnert, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a more recent study indicated that the association between OA participation and positive adjustment was stronger as OA intensity increased, even among youth participating in 20 or more hours/week (Mahoney and Vest 2012). Conversely, other studies have demonstrated elevated negative outcomes such as poorer academic performance and more depressive symptoms and loneliness as intensity of OA involvement exceeded a critical threshold (Knifsend and Graham 2012;Randall and Bohnert 2009;Randall and Bohnert 2012;Rose-Krasnor et al 2006). However, over-scheduling effects may vary by gender (Luthar et al 2006;Randall and Bohnert 2012).…”
Section: Introductionmentioning
confidence: 87%
“…However, over-scheduling effects may vary by gender (Luthar et al 2006;Randall and Bohnert 2012). For example, Luthar et al (2006) found over-scheduling effects only among females highly involved in academic activities and Randall and Bohnert (2012) demonstrated that high levels of OA involvement were negatively associated with psychological (i.e., depressive symptoms) and social (i.e., making close friendships) outcomes, but only for male participants.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation